The Design of IoT Based Lighting Installation Tools in Electrical Installation Engineering and Microcontroller Systems Courses - Kurniawan Kurniawan; Sri Wahyuni; Mursyidin Mursyidin (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
Internet of Things (IOT)-based lighting installation development Since teaching aids are an exact science, it is essential to have a tool that can depict the subject covered in the Electrical Installation Engineering course. The teaching tools created are meant to help lecturers better present the topic for electrical installation engineering to their students while also making it simpler for them to comprehend. In order to turn on and off lights and outlets using a smartphone and a manual switch in the event that the wifi network is damaged, this study added Internet of Things (IOT) installation procedures and a swap switch. The Research & Development approach is being used in this investigation. A validation sheet is created by planning and creating research instruments, which is what is done to test the viability of instructional aids by professional validators. According to the results of expert validation, this teaching tool is appropriate for use with media and material experts based on the percentage values of media expert 1 receiving a score of 94.28% and media expert 2 receiving a score of 97.14%, and for material expert 1 receiving a score of 90% and material expert 2 receiving a score of 92%, with the category "Very Eligible".